Social enterprise in Europe: At the crossroads of market, public policies and third sector - Defourny, Jacques; Nyssens, Marthe (Policy & society, 2010)
Over the last 15 years, the concept of social enterprise has been raising an increasing interest in various regions of the world. In the present paper, we describe, first, the European historical landscapes in which the concept of social enterprise took root. In the second part, we analyze the various public policies introduced in several European countries. In the third part, we analyse the logics of financing of social enterprises. Based on the EMES conception of social enterprise, we underline the “hybridization” of their resources. European social enterprises indeed, most often, combine income from sales with public subsidies linked to their social mission and private donations and/or volunteering. This clearly contrasts with a strong US tendency to define social enterprises as non-profit organizations more oriented towards the market and developing “earned income strategies” as a response to decreasing public subsidies and to the limits of private grants from foundations.